1989
DOI: 10.2172/5148213
|View full text |Cite
|
Sign up to set email alerts
|

A historical review of portable health physics instruments and their use in radiation protection programs at Hanford, 1944 through 1988

Abstract: Waste Management Radioactive Shipments4.2 TECHNIQUES AND TRAINING . As the need for production of special nuclear materials for defense purposes diminished and long-time Hanford workers began to retire, the decision was made to document Hanford's experience with portable health physics instruments while the resources to do so were still available. In 1989, only a few health physics instrument specialists, radiation technicians and health physicists who worked at Hanford in the late 1940s still live in the vici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…These gaps resulted from limited photon measurements that could be paired to the neutron measurements. Howell et al (1989) was found to be an excellent source of information concerning the historical timeline of the different neutron survey instruments used at Hanford.…”
Section: Data Codingmentioning
confidence: 99%
“…These gaps resulted from limited photon measurements that could be paired to the neutron measurements. Howell et al (1989) was found to be an excellent source of information concerning the historical timeline of the different neutron survey instruments used at Hanford.…”
Section: Data Codingmentioning
confidence: 99%
“…In addition to the SuperDads, the high-range totem pole ion chamber survey instruments were removed from service. The instruments, circa 1954 (Howell et al 1989), were supplied to field organizations as part of emergency response kits. When facilities ceased using the PNNL-supplied emergency response kits, there was no longer a demand for the high-range totem pole instruments.…”
Section: Administration Of Portable Instrument Poolmentioning
confidence: 99%